1998
DOI: 10.1080/02839319850163039
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychosocial Work-related Risk Factors Associated with Musculoskeletal Symptoms among Home Care Personnel

Abstract: The aim of this cross-sectional study was to investigate physical and psychosocial aspects of the work environment, sociodemographic data and certain lifestyle factors, and the relationship between these variables and complaints in the shoulder/neck and low back area among female home care personnel. A questionnaire was completed by 361 randomly selected women. Multiple logistic regression analyses were conducted to evaluate the importance of several exposure factors for complaints in the shoulder/neck and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 15 publications
4
34
1
Order By: Relevance
“…Worry about work conditions was assessed by ten questions on worry about different work conditions that were taken from a study conducted on home care personnel (Brulin et al 1998) and adapted to ambulance personnel. These questions addressed worry about physical and psychological factors as well as medical competence.…”
Section: Questionnairementioning
confidence: 99%
“…Worry about work conditions was assessed by ten questions on worry about different work conditions that were taken from a study conducted on home care personnel (Brulin et al 1998) and adapted to ambulance personnel. These questions addressed worry about physical and psychological factors as well as medical competence.…”
Section: Questionnairementioning
confidence: 99%
“…The etiology of low back pain (LBP) and neck/shoulder pain (NSP) is multifactorial (Brulin et al, 1998;Burdorf and Sorock, 1997;Linton, 2001;Malchaire et al, 2001). Psychosocial factors like low job satisfaction and lack of social support have been found related to LBP and NSP among nurses (Lagerstrom et al, 1998;Smedley et al, 2003;Yip, 2001) and physical load like patient handling tasks have been associated with LBP, NSP (Engels et al, 1994b;Hignett, 1996b;Hui et al, 2001;Lagerstrom et al, 1998;Smedley et al, 1998;Yip, 2001), as well as knee pain (KP) (Menzel et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…heart rate, movements or muscle activity by use of electromyography measurements (EMG), lumbar motion monitor and calculated lumbar compression forces/shear forces (Marras et al, 1999(Marras et al, , 2005Nuikka et al, 2001;Schibye et al, 2003), observations (e.g. OWAS, REBA, PEO) (Engels et al, 1994a;Hignett, 1996a;Hignett and McAtamney, 2000) or by retrospective self-reported questionnaires (Ando et al, 2000;Brulin et al, 1998;Hui et al, 2001;Smedley et al, 1995;Trinkoff et al, 2003;Yip, 2001). Estimations of load, posture or activities are often based upon questions about the average working day or a defined working period (Eriksen et al, 2004;Maul et al, 2003;Smedley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The physical work environment was assessed by means of indices that were found to be associated with shoulder neck and low back complaints in a previous study (17). These indices were ''lifting in awkward positions'' and ''standing in awkward postures''.…”
Section: Questionnairementioning
confidence: 99%